Design of a sustainable, intelligent and interconnected food container following Cradle to the Cradle principles and using Life Cycle Analysis for the evaluation of environmental impacts (INNOTEC, 2019)
The main objective of the present work is to help combat food waste, which is one of the main problems of the food industry today, incorporating also sustainability concepts. According to the FDA each year about 1,300 million tons of food are thrown. Food is wasted mainly at household levels, which is why the choice of the sustainable design of an intelligent interconnected packaging for domestic use is made. To achieve this, the exploration of different technologies, materials, methodologies and innovative frameworks is carried out. Regarding materials, the possibility of using biodegradable, recycled, recyclable and bioplastics was studied, along with the research of the intelligent technology to use, which ended up being sensors. As to methodologies, Life Cycle Analysis (LCA) and Cradle to Cradle philosophy (C2C) are deeply studied. Intelligent packaging systems are an option to contribute to minimization of food waste. The correct use of tools such as the LCA, along with the principles of the C2C, and the research on materials and technologies to be used can help designers to reach an optimal solution, minimizing environmental impacts.
Keywords: Circular economy; environmental impact; ecodesign; smart packaging; food industry